2011
DOI: 10.3892/ol.2011.362
|View full text |Cite
|
Sign up to set email alerts
|

A genomic approach to investigate expression profiles in Slovenian patients with gastric cancer

Abstract: Abstract. Despite its decreasing frequency in developed countries, gastric cancer remains a significant health burden. The aim of the present study was to construct cDNA libraries and analyze differentially expressed genes related to this disease. Gene expression profiles were generated with suppressive subtraction hybridization (SSH). We constructed eight SSH libraries, four representing up-regulated genes and four representing down-regulated genes in tumor tissues. Our approach revealed that several genes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…It has been demonstrated that loss of BUB3 gene function could lead to chromosomal instability [Mendoza et al, 2005]. Interestingly, overexpression of BUB3 has also been described in gastric cancer [Grabsch et al, 2003;Hudler et al, 2011]. It has been demonstrated that there is a strong correlation between the level of BUB expression and tumor cell proliferation [Grabsch et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that loss of BUB3 gene function could lead to chromosomal instability [Mendoza et al, 2005]. Interestingly, overexpression of BUB3 has also been described in gastric cancer [Grabsch et al, 2003;Hudler et al, 2011]. It has been demonstrated that there is a strong correlation between the level of BUB expression and tumor cell proliferation [Grabsch et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these pathways were initially discovered to be active during embryogenesis, but recent research showed that they are also involved in regeneration process of gastric mucosa [87]. As expected, global expression analyses showed aberrant expression of many genes, which differ among individuals, but are implicated in the same signalling networks [45, 8791]. Furthermore, there is a complex interplay between environmental factors and these pathways that remains to be elucidated.…”
Section: Deregulation Of Signalling Pathwaysmentioning
confidence: 95%
“…It was shown that AURKA overexpression overrides the mitotic spindle checkpoint and leads to incomplete cytokinesis, multinucleation, and multipolar spindles [ 43 , 44 ]. Other important regulators of cell cycle progression, such as CCNB1, CCNE1, PTTG1, and PLK, have also been found overexpressed in gastric carcinomas and associated with poor prognosis [ 45 48 ].…”
Section: Chromosomal Instability (Cin)mentioning
confidence: 99%
“… 1 , 2 It is believed that complex interplay of genetic and environmental factors triggers the accumulation of numerous genetic and epigenetic alterations in cells, resulting in deregulation of normal cell functions and disruption of stomach linen homeostasis. 3 - 6 Individual genetic factors probably contribute to aberrant processes in the genesis of malignant phenotype. Among them, single nucleotide polymorphisms (SNPs) and other genetic variants play an important role as the main genetic elements in the aetiology of several complex diseases, including gastric cancer.…”
Section: Introductionmentioning
confidence: 99%